Pembinaan Pengrajin Sapu Ijuk di Dusun Krajan Desa Kanigoro Kecamatan Pagelaran Kabupaten Malang - Asroful Anam; Teguh Rahardjo; Ni Putu Agustina (University of Merdeka Malang, 2020)
The prosperous and decent to need of both primary and secondary necessaries life are absolutely needed by every family. So they endeavor to increase their abilities to obtain subsist prosperity by entrepreneurship, as handicraft businesses, palm broom, that made by people in Krajan Hamlet, Kanigoro Village, Pagelaran District, Malang Regency. But for reaching the independent business, they meet many obstacles, such as producted quality lower than factory production; low market opportunities, and business governance out of standardized. Constraints faced by palm broom craftsmen in Krajan Hamlet, Kanigoro Village, occur without guidance and attention from the government. So that we as academics/lecturers take the initiative to foster the broom fibers craftsmen through the Community Service Program in order to improve the quality of their products, penetrate the wider market, and home industry management with good governance. This Community Service method used completely ongoing coaching. Based on the results of that implementation, the product can compete with the factory product broom; an increase in the market, and an increase in the welfare of the craftsman family. By this, creating a good governance management of home industry, and making young adults interest to maintain the palm broom. DOI: https://doi.org/10.26905/abdimas.v5i2.4000